Opinia . pismo Ruchu Praw Człowieka i Obywatela w Polsce, no. 45-46, 1981 - [ed. Jerzy Brykczyński et al.] ([s.n.], 1981)
Creation and circulation: Journal republished legally in 1990; Some numbers published in various versions, both single- and double-sided, also in 21 cm. format